2021
DOI: 10.2196/26360
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Assessment Tools for Military Personnel With Mild Traumatic Brain Injury: Scoping Literature Review

Abstract: Background Mild traumatic brain injury (mTBI) occurs at a higher frequency among military personnel than among civilians. A common symptom of mTBIs is cognitive dysfunction. Health care professionals use neuropsychological assessments as part of a multidisciplinary and best practice approach for mTBI management. Such assessments support clinical diagnosis, symptom management, rehabilitation, and return-to-duty planning. Military health care organizations currently use computerized neurocognitive as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…It may be that glucose uptake would more strongly correlate with other metrics of functioning. Some have suggested that computerized tests that precisely assess accuracy and processing speed may be more sensitive to neuropsychological decline than standard neuropsychological tests (Jones et al, 2021). Particularly given the relatively high functioning of the sample (Full Scale Intelligence Quotient [FSIQ] = 110), we may have found significant results using computerized tests, though it is also noted that these tests have not been shown to have acceptable reliability, validity, and clinical utility in military mTBI (Jones et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that glucose uptake would more strongly correlate with other metrics of functioning. Some have suggested that computerized tests that precisely assess accuracy and processing speed may be more sensitive to neuropsychological decline than standard neuropsychological tests (Jones et al, 2021). Particularly given the relatively high functioning of the sample (Full Scale Intelligence Quotient [FSIQ] = 110), we may have found significant results using computerized tests, though it is also noted that these tests have not been shown to have acceptable reliability, validity, and clinical utility in military mTBI (Jones et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that computerized tests that precisely assess accuracy and processing speed may be more sensitive to neuropsychological decline than standard neuropsychological tests (Jones et al, 2021). Particularly given the relatively high functioning of the sample (Full Scale Intelligence Quotient [FSIQ] = 110), we may have found significant results using computerized tests, though it is also noted that these tests have not been shown to have acceptable reliability, validity, and clinical utility in military mTBI (Jones et al, 2021). It is also possible that glucose uptake would be more likely to show a relationship with cognition if the patient performed the cognitive task during the scan, rather than at a separate time.…”
Section: Discussionmentioning
confidence: 99%
“…A concussion is defined as a temporary impairment of brain function caused by trauma to the head; the duration of the accompanying memory loss is mostly less than 24 h [20], and the vast majority of patients will achieve complete relief of symptoms within 7-10 days [21]. A commonly used psychometric tool for assessing the severity of concussion is the Glasgow Coma Scale (GCS), which mainly evaluates verbal and motor responses, as well as the ability to open eyes, and it can be used to initially determine the severity of concussion.…”
Section: Concussion and Blast Injurymentioning
confidence: 99%
“…A recent scoping review (Jones et al, 2021) of the neurocognitive assessment tools (NCATs) revealed that the NCATs mostly used among the 33 studies were "Automated Neuropsychological Assessment Metric" (46%), "Defense Automated Neurobehavioral Assessment" (15%), and "Immediate Post-Concussion Assessment and Cognitive Testing" (10%). However, one challenging finding was that the diagnosis of mTBIs varied across all studies (and that could affect validity).…”
Section: Computerized Neuropsychological Assessmentmentioning
confidence: 99%
“…However, one challenging finding was that the diagnosis of mTBIs varied across all studies (and that could affect validity). One of the recommendations was that NCATs should be used cautiously and "only as one source of information from many other types of clinical tools and observations" (Jones et al, 2021).…”
Section: Computerized Neuropsychological Assessmentmentioning
confidence: 99%